Calculation of Pension Funds for TNI Group IIIA Using the Individual Level Premium Method - Bisyarah, Sania; Novi Elizabeth S., Sri (International Journal of Mathematics, Statistics, and Computing, 2024)
Prosperity in retirement is one of the important aspects to achieve in the career path of every individual, including the Indonesian National Army (TNI) which relies on pension funds as a source of post-retirement income. Pension funds manage programs that promise financial benefits to participants after they retire. In this context, the study aims to present the calculation of pension funds for TNI class IIIA using the Individual Level Premium method. This method allocates the total pension benefit equally each year. As a result, it is found that the Individual Level Premium method provides a greater pension benefit value than the benefit value using the proportion of salary from ASABRI. This shows that this method is effective in calculating retirement benefits.